2014
DOI: 10.1039/c3dt53340a
|View full text |Cite
|
Sign up to set email alerts
|

Structure and thermal expansion of the tungsten bronze Pb2KNb5O15

Abstract: The structure and thermal expansion behavior of the tetragonal tungsten bronze oxide Pb2KNb5O15 were investigated by neutron powder diffraction and high-temperature X-ray diffraction. Below the Curie temperature, T(C) (orthorhombic phase, T(C) ≈ 460 °C), the cell parameters a and c increase with temperature, while b decreases. The thermal expansion coefficients are α(a) = 1.29 × 10(-5) °C(-1), α(b) = -1.56 × 10(-5) °C(-1), and α(c) = 1.62 × 10(-5) °C(-1). Temperature-dependent second harmonic generation (SHG),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 48 publications
2
42
0
Order By: Relevance
“…The family of tetragonal tungsten bronze (TTB) materials, evidenced since 1949 and intensively studied both as single crystals and as ceramics [1][2][3][4][5][6][7], exhibits exceptional ferroelectric behaviors [8,9], together with non-linear optical properties. These features make them interesting materials for electro-optics and optoelectronics [1,[10][11][12][13][14][15][16] as well as promising candidates for computer memory applications based on resistive switching phenomena [17,18]. An additional advantage of these materials is the large variety of atoms present in their cell, which permit many chemical substitutions giving rise, for instance, to the possibility to give magnetic properties to these structures.…”
Section: Introductionmentioning
confidence: 99%
“…The family of tetragonal tungsten bronze (TTB) materials, evidenced since 1949 and intensively studied both as single crystals and as ceramics [1][2][3][4][5][6][7], exhibits exceptional ferroelectric behaviors [8,9], together with non-linear optical properties. These features make them interesting materials for electro-optics and optoelectronics [1,[10][11][12][13][14][15][16] as well as promising candidates for computer memory applications based on resistive switching phenomena [17,18]. An additional advantage of these materials is the large variety of atoms present in their cell, which permit many chemical substitutions giving rise, for instance, to the possibility to give magnetic properties to these structures.…”
Section: Introductionmentioning
confidence: 99%
“…For CBN compounds, the bigger Ba 2+ ions (1.61 Å) occupy the 15-fold coordinated oxygen octahedral A2 sites, the relative smaller Ca 2+ ions (1.34 Å) mainly occupy the 12-fold coordinated oxygen octahedral A1 sites [20,21]. Then the TTB structure with only five A-sites are occupied out of six and it results in a socalled 'unfilled' structure that is responsible for charge disorder and relaxor behavior [12,14,16].…”
Section: Introductionmentioning
confidence: 96%
“…In the recent years, some studies have shown the increasing interest of materials with tetragonal tungsten bronze (TTB) structure by demonstrating their potential technological applications [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…It has an orthorhombic structure at room temperature with cell parameters: a=17.754 (2) Å, b = 18.014(2) Å and c = 3.915(1) Å [8]. PKN ceramic presents a behavior of a classical ferroelectric and undergoes a ferroelectric-paraelectric phase transition at Tc=450 °C [9], changing the point symmetry from P4/mbm (N° 127, paraelectric) to Cm2m (N° 38, ferroelectric). At room temperature PKN is ferroelectric and ferroelastic as refined by Sciau et al [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation